Cambridge anticipations of the natural rate hypothesis? Robertson and Champernowne revisited - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2018)
The "natural rate hypothesis" is usually ascribed to ideas put forward by M. Friedman and E. Phelps between 1966 and 1968. It postulates that changes in nominal aggregate demand affect aggregate output because agents cannot temporarily distinguish relative from general price movements when they face imperfect information. This paper shows how some of its key conceptions may be found in contributions by Cambridge economists D.H. Robertson and D.G. Champernowne advanced in the 1930s as critical responses to J.M. Keynes's General Theory. Robertson and Champernowne devised the concepts of "normal" and "basic" unemployment rates respectively, expressed as equilibrium positions when workers' real wage expectations are satisfied. Robertson combined that with his previous discussion of monetary misperceptions, whereas Champernowne argued how equilibrium may be achieved through inflation/deflation acceleration. Unemployment homes in on its "natural" equilibrium level only if the market rate of interest converges to its (Wicksellian) natural rate, as Robertson stressed.
Keywords: B22; B30; E31; E32; 330; natural rate hypothesis; Robertson; Champernowne; basic unemployment; normal output; acceleration